2019
DOI: 10.1186/s12906-019-2702-6
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates peritoneal fibrosis via inhibition of transforming growth factor-activated kinase 1 (TAK1) pathway in a rat model of peritoneal dialysis

Abstract: Background: Peritoneal fibrosis (PF) remains a serious complication of long-term peritoneal dialysis (PD). The goal of this study was to investigate the anti-fibrotic effects of curcumin on the PF response to PD and its' mechanism. Methods: Male Sprague-Dawley rats were infused with 20 mL of 4.25% glucose-based standard PD fluid for 8 consecutive weeks to establish PF model and then divided into five groups: Control, received sham operation and 0.9% physiological saline; PD, received 4.25% standard PD fluid; C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…31 On the other hand, Notch3 exhibited anti-fibrotic effect through inhibiting the expression of α-SMA. 32 Similar to these results, silencing of PVT1 could suppress renal fibrosis via inactivation of α-SMA in TGF-β1-treated HK-2 cells. In addition, E-cadherin and α-SMA played crucial roles in EMT process.…”
Section: Discussionsupporting
confidence: 75%
“…31 On the other hand, Notch3 exhibited anti-fibrotic effect through inhibiting the expression of α-SMA. 32 Similar to these results, silencing of PVT1 could suppress renal fibrosis via inactivation of α-SMA in TGF-β1-treated HK-2 cells. In addition, E-cadherin and α-SMA played crucial roles in EMT process.…”
Section: Discussionsupporting
confidence: 75%
“…So, targeting TGF-β1 can ameliorate PD-mediated fibrosis. The administration of curcumin remarkably reduces the expression of TGF-β1 in PD animal models to improve ultrafiltration volume, diminish mass transfer of glucose and fibroproliferative response (Zhao et al, 2019a). It seems that during PD, TGF-β signaling pathway enhances migration and motility of cells via stimulation of EMT.…”
Section: Fibrosismentioning
confidence: 99%
“…Studies have demonstrated that curcumin can inhibit TGF-β1-induced CTGF expression by disrupting Smad2 signaling and can also suppress CTGF through the inhibition of the c-Jun NH(2)-terminal kinase (JNK) signaling pathway in fibroblasts [ 37 , 38 ]. In a rat model of peritoneal fibrosis, Zhao and colleagues elucidated that the inhibitory action of curcumin on TGF-β signaling is mediated, at least in part, through the suppression of the Transforming Growth Factor-Activated Kinase 1 (TAK1) pathway [ 39 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%